Peningkatan Kinerja SDM di Divisi Maintenance Bandara Hang Nadim dalam Era Transformasi - Sarmini, Sarmini; Windayati, Diana Titik; Yuniar, Indhiawan (Zona Manajerial: Program Studi Manajemen (S1), 2025)
The challenges faced by the company after the Covid-19 pandemic hit, including the recovery of the condition of the airport management company, in this case PT Bandara International Batam. This study aims to determine the condition and implementation of appropriate HR strategies and to maintain the continuity of the company's business continuity. Using a qualitative approach, the problem of declining performance and HR readiness was found to be the main problem of supporting work equipment and a lack of training for employees. Therefore, support is needed to overcome this by providing work support equipment and conducting training according to their fields to increase knowledge and can create and compile SOPs so that employee performance issues and maintenance activities can work well and the speed of handling disruptions can be faster. In addition, several important things that serve as input for the company. Among them, the company focuses on cost efficiency by optimizing the mastery and use of IT technology. Increasingly developing towards a digital era combined with new literacy skills. And the company can reduce business expenses while maintaining good customer service. Where transformation is balanced with the speed of HR adaptation, HR needs to learn new skills to stay relevant, and leadership provision